THE THEORY OF BILINGUALISM IN THE ASPECT OF NEUROLINGUISTICS - Ergashova , Munavvar Dilsiroj qizi (Educational Research in Universal Sciences, 2023)
Given that every person has a unique set of bilingual traits; it might be difficult to sum up bilingualism in a few words. There could be disparities in a language’s aptitude and use, or in the level of expertise between the two languages. Most people learn to speak two languages because they find it useful in their daily activities. As a result, each person’s level of bilingualism will be unique. Although it is relatively typical to have a dominant language, bilinguals are not always completely fluent in both of their languages. It should be mentioned that learning to communicate in two languages takes time. One cannot become bilingual after studying a language for six months. Information on bingualism hypothesis is included in this article.